STRATEGIES FOR THE EXPLOITATION OF RESIDUAL OILS IN BIOFUEL PRODUCTION: REVIEW OF TECHNOLOGIES, ENVIRONMENTAL BENEFITS AND CHALLENGES - Casanova Pazmiño, Anthony; Dueñas Rivadeneira, Alex Alberto (Centro Azúcar Journal, 2026)
Introduction: Vegetable oil is an organic compound composed mainly of triglycerides. Its widespread use in the food industry generates large volumes of highly polluting waste. However, this waste represents a strategic opportunity to produce biodiesel, a sustainable alternative to fossil diesel that mitigates energy dependence and environmental impact within a circular economy model. Objective: To analyze strategies for utilizing waste oils, evaluating their conversion technologies, ecological benefits, and technical challenges for industrial scalability. Materials and Methods: A systematic literature review was conducted in academic databases, selecting relevant technical and scientific literature using inclusion criteria to identify synthesis processes and reported results. Results and Discussion: The research confirms that used oils are a viable raw material for biodiesel. Transesterification and advanced catalytic processes stand out for their efficiency. The use of these wastes significantly reduces emissions and improves waste management; however, collection logistics, pretreatment, and operating costs limit their mass implementation. Conclusions: The use of waste oils is an effective and sustainable solution. Despite its potential to reduce pollution, its scalability depends on overcoming financial and logistical barriers, with regulatory support and continuous technological innovation being crucial.